Beelden kijken. (Antwerpen : Openluchtmuseum voor beeldhouwkunst Middelheim, 1978)
Rodin ; Wouters, Rik ; Duchamp-Villon ; Maillol, A. ; Lipchitz, J. ; Laurens, H. ; Gargalo, P. ; Bill, Max ; Wotruba, Fritz ; Moore, Henri ; Steinbrenner, H. ; Hepworth, B. ; Penalba, A. ; Calder, A. ; Gentils, Vic ; Soto, J.R. ; Martini, A. ; Bodmer, W. ; Fazzini, P.
boek